VERBA BERPELENGKAP DALAM BAHASA INDONESIA SUATU KAJIAN STRUKTUR DAN SEMANTIK - Karlieni, Eni (LITERA, 2005)
This research study attempts to describe morphological forms of verbs with complements in Indonesian and their syntactic and semantic characteristics. The method employed in this study was the descriptive one, which was synchronically applied. The data sources were Indonesian textbooks for elementary schools, junior high schools, and senior high schools, besides newspapers such as Kompas, Republika and Pikiran Rakyat. Morphologically, verbs with complements can be free verb bases, derived verbs, and reduplicated verbs. On the basis of their syntactic characteristics, the verbs can be those with noun complements (noun phrases), verbals (verbal phrases), adjectives (adjectival phrases), adverbials (adverbial phrases), and numbers (numeral phrases). On the basis of their semantic characteristics, the verbs can be classified into punctual verbs, dynamic verbs, and static verbs. Keywords: argument, complement, constituent